Building an Android-Based Application for Schedule Reminders for Students' Assignments at SMKS Sri Langkat Tanjung Pura with Encryption and Decryption Processes Using the RSA Algorithm - Armenda, Risma; Achmad Fauzi; Juliana Naftali Sitompul, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research aims to solve the problems faced by students of SMKS Sri Langkat Tanjung Pura in organizing their schedules and assignments, while protecting their personal data. An Android-based schedule reminder application was created as a solution to better manage assignments. To ensure the confidentiality and security of sensitive data such as assignment files, this research uses the RSA (Rivest-Shamir-Adleman) cryptographic algorithm in the encryption and decryption process. This application is designed so that students can manage their assignments in an orderly and efficient manner, with the hope of improving the quality of education and reducing the level of negligence. The methodology applied includes system requirements analysis, system design using flowcharts and UML, and system testing to ensure the application functions properly. The implementation of this application is carried out using Android Studio with the Java programming language and the phpMyAdmin database. As a result, this application not only provides a practical solution for students in managing assignments, but also contributes to the field of computer science in the development of mobile applications and data security.